Дороги жизни: [стихи, эссе] / Григорий Кораблев - Кораблев Григорий Андреевич (ИД Удмуртский университет, 2010)
Экземпляры: ф.10 (20171017) / Инвентарный номер: 57736 / Цена: / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: К 66 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6-5